Association between maternal emotion socialization and emotion regulation in early adolescents with elevated internalizing symptoms: insights from multi-informant discrepancies - Zhao, Junxuan; Pozzi, Elena; Lin, Sylvia Chu; Kehoe, Christiane E.; Havighurst, Sophie S.; Whittle, Sarah (Frontiers in Psychiatry, 2025)
IntroductionAlthough the relationship between parental emotion socialization and emotional competence, including emotion regulation, in children and adolescents has been extensively explored, there is a lack of research investigating this association in adolescents at high risk for mental health problems. The present study examined the association between maternal emotion socialization and emotion regulation in adolescents with high levels of internalizing symptoms, using multi-informant measurements (mother-reported, adolescent-reported, observer-reported). The study also explored whether discrepancies in the report of parental emotion socialization by different informants were related to adolescent emotion regulation, in addition to factors that may contribute to informant discrepancies.MethodsParticipants were 70 female adolescents (mean age = 11.46 years, SD = 0.77) with high levels of internalizing symptoms and their mothers. Maternal emotion socialization (i.e., emotion dismissing and emotion coaching) was assessed using mother- and adolescent-reported questionnaires, and via observation during an emotion discussion task. Adolescent emotion regulation was reported by mothers and adolescents, while maternal emotion regulation was self-reported. ResultsAdolescent-reported maternal emotion coaching and dismissing were significantly related to adolescent-reported adolescent emotion regulation. Informant discrepancies were not related to adolescent emotion regulation. Mothers higher in emotion regulation difficulties reported that their emotion coaching was more congruent with adolescent- and observer-reported emotion coaching, although this effect did not reach statistical significance. DiscussionOur findings highlight the value of adolescent-reported variables in parenting and adolescent emotion research. Additionally, mothers’ emotion regulation may influence their assessments of their emotion socialization behaviors.